Influence of fiber volume fraction and aspect ratio in Resol-Sisal composites - García Zárate, Joaquín (2003)
Vegetable fibers are being used as reinforcements in polymeric matrices with a wide variety of applications. Among these fibers, sisal is of particular interest due to the high impact strength and moderate tensile and flexural properties of its derivated composites. Because of its low cost and affinity, a phenol-formaldehyde resin, resol, has been selected as the matrix to obtain resol-sisal composites. The influence of fiber length and volume fraction on flexural properties has been studied. An optimum for the fiber length as well as for the fiber volume fraction was found. The improvement of the properties occurred up to a length of about 23 mm. The use of longer fibers lead to reduced properties because they tended to curl and bend during processing. Besides, actual composite densities were lower than theoretical ones mainly due to the presence of voids. This undesirable porosity produced a reduction in flexural properties at high fiber contents.